Application-independent protocol for predicting the efficiency of lithium-ion battery cells in operations. (February 2018) - Brivio, C.; Musolino, V.; Alet, P.-J.; Merlo, M.; Hutter, A.; Ballif, C.
Abstract: Despite a continuous reduction in battery prices, investment in storage systems carries a high risk. Indeed, many applications lack an adequate test protocol and method to predict the performance of batteries in operations. In this paper, we focus on lithium-ion battery energy storage systems (BESS), for which we introduce a novel method. With this method, predicting the efficiency of lithium-ion BESS becomes possible for any application from a single set of measurements. We show that evaluating the battery resistance as a function of the C-rate provides general "capability charts" based on which the efficiency can be evaluated under arbitrary operation profiles. Application-specific test procedures therefore become unnecessary. We have applied the novel procedure on three different lithium-ion cell technologies and illustrate its accuracy in the example of grid-connected BESS used for primary control reserve.